The Correlation Between Burnout And Effectiveness Of Nurses In Shiraz Nemazee Hospital - Tahereh Shafaghat; Mohammad Kazem Rahimi Zarchi; Zahra Kavosi (Tehran University of Medical Sciences, 2015)
Background and Aim: The main purpose of all organizations is improving efficiency and effectiveness. One of the barriers of reaching effectiveness is burnout which can be seen as the final outcome of job stress in many professions including nursing. This study aimed to evaluate the correlation between effectiveness of nurses and burnout in Shiraz Nemazee hospital. Materials and Methods: This descriptive-analytic and cross-sectional study was done among all of the nurses in the Shiraz Nemazee hospital. Two hundred and forty five nurses were selected using random classified sampling method. The data gathering form was standardized questionnaire. Data were entered into SPSS 15 software and the Pearson correlation test was used for data analysis. Results: The study nurses were at moderate level according to burnout and effectiveness variables. There were positive correlation between "effectiveness" and "target acquisition" and "preservation of the cultural model" dimensions with "lack of individual success" dimension (P<0/05). Also, there was a negative correlation (P<0/05) between burnout in nurses and their effectiveness. Conclusion: It seems that nurses' burnout can affect their effective performance so managers can enhance effectiveness of staff performance by providing programs to reduce burnout and its dimensions.